Inverse initial boundary value problem for a non-linear hyperbolic partial differential equation. (16th December 2020) - Nakamura, Gen; Vashisth, Manmohan; Watanabe, Michiyuki
Abstract: In this article we are concerned with an inverse initial boundary value problem for a non-linear wave equation in space dimension n ⩾ 2. In particular we consider the so called interior determination problem. This non-linear wave equation has a trivial solution, i.e. zero solution. By linearizing this equation at the trivial solution, we have the usual linear wave equation with a time independent potential. For any small solution u = u ( t, x ) of our non-linear wave equation which is the perturbation of linear wave equation with time-independent potential perturbed by a divergence with respect to ( t, x ) of a vector whose components are quadratics with respect to ∇ t, x u ( t, x ). By ignoring the terms with smallness O (|∇ t, x u ( t, x )| 3 ), we will show that we can uniquely determine the potential and the coefficients of these quadratics by many boundary measurements at the boundary of the spacial domain over finite time interval and the final overdetermination at t = T . In other words, our measurement is given by the so-called the input-output map (see (1.5 )).